EVALUASI PENERAPAN PSAK 55 (MENGENAI INSTRUMEN KEUANGAN: PENGAKUAN DAN PENGUKURAN) PADA PENURUNAN NILAI DAN TIDAK TERTAGIHNYA ASET KEUANGAN, PERLAKUAN AKUNTANSI, DAN NILAI PERUSAHAAN (STUDI KASUS PAD PT.ABC VENTURA) - Muhammad Evan Secarian; Endang Kiswara (Diponegoro Journal of Accounting, 2012)
The aim of this research was to analyze the implementation of PSAK 55 Financial Instrument: Recognition and Measurement and focuses on Impairment of Financial Assets Measured at Amortized Cost had used by PT. ABC Ventura based on PSAK 55, accounting treatments and company value with book value method. This study was conducted with qualitative methods through a case study on PT. ABC Venture by interviewed staff and president and do library research obtained directly from the company and another object. The results of this study indicates that PT.ABC Ventura was implementing PSAK 55 and obey the standards, accounting treatment has been implemented with good and the impact of that is financial statement can be reliable for customer and shareholder, and know the company value of PT.ABC venturwewith book value method.